New Power Structures and Shifted Governance Agendas Disrupting Climate Change Adaptation Developments in Kenya and Uganda - Julia Renner (Sustainability, 2020)
Kenya and Uganda are currently two of the fastest growing countries in the East African Community. The political leaderships’ prioritization of sociopolitical and economic development, combined with the wish for a closer integration into the world market, shifted the countries’ governance structures and agenda setting. Undertaken economic projects, including oil explorations, mining and gold extractions, flower farming and intense rice growing, put conservation areas at great risk and led to a decrease of the country’s wetland and forest cover. Accordingly, the impact of climate change on the vulnerability of countries is increasing. The paper critically investigates how particularly recent economic investments by national and international companies question the coherence between the institutional framework on climate policies, especially on a sub-national level of decision-making. Based on two field visits to the area, this paper raises the question of how the institutional frameworks shape climate governance processes in Kenya and Uganda. Looking at both political and climate governance structures from a pragmatic perspective, this paper concludes that the insufficient implementation of existing governance structures hampers the better integration of climate policies. National actors do not consider climate financing as an important issue which results in the fragmentation and undermining of climate policy processes.